2017
DOI: 10.1186/s12877-017-0493-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation and psychometric properties of the commitment to hip protectors (C-HiP) index in long-term care providers of British Columbia, Canada: a cross-sectional survey

Abstract: BackgroundIf worn during a fall, hip protectors substantially reduce risk for hip fracture. However, a major barrier to their clinical efficacy is poor user adherence. In long-term care, adherence likely depends on how committed care providers are to hip protectors, but empirical evidence is lacking due to the absence of a psychometrically valid assessment tool.MethodsWe conducted a cross-sectional survey in a convenience sample of 529 paid care providers. We developed the 15-item C-HiP Index to measure commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Outcome variables include physician reported personal and facility-level change in preference regarding unrelated donor graft use from peripheral blood source to bone marrow. These survey items were scored on a 5 -point Likert scale from very important to very unimportant Reliability: Not reported; Validity: Not reported Korall, 2017, 2018 [ 64 , 65 ] One study—two reports Canada 13 long-term care homes Cross-sectional study Paid care providers = 529 Age in years ( n (%)): 20–29 = 42 (7.9%); 30–39 = 87 (16.4%); 40–49 = 149 (28.2%); 50–59 = 187 (35.3%); 60–69 = 46 (8.7%); Missing/unknown = 18 (3.4%) Reported Gender: Female = 474 (89.6%); Male = 40 (7.6%); Missing/unknown = 15 (2.8%) Interpreted as: Sex Professions: Health care assistant/resident care aide = 290 (54.8%); Licensed practical nurse = 84 (15.9%); Registered nurse = 40 (7.6%) Resident care coordinator = 13 (2.4%); Manager = 14 (2.6%); Recreational/occupational/ physiotherapist = 24 (4.5%); Unit/program clerk = 18 (3.4%); Missing/unknown = 49 (9.3%) Innovation: Hip protectors are protective undergarments with either a hard shield or soft pads sewn into its sides to cover the skin over the lateral aspects of the proximal femur. The purpose of hip protectors is to minimize the injury to the hip resulting from a fall Study outcome measurement Measures: A 15-item questionnaire titled as C-Hip Index, developed and tested for psychometric properties by authors [ 64 ] to measure affective and cognitive, behavioural and overall hip protector commitment Reliability: α (range) = 0.87–0.97 Validity: (1) Construct validity: Authors reported a two-factor structure as the result of an exploratory factor analysis: Factor 1 (affective and cognitive commitment) and Factor 2 (behavioural commitment) which loaded to a higher order factor called "commitment to hip protectors" with an eigen value of 1.386.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Outcome variables include physician reported personal and facility-level change in preference regarding unrelated donor graft use from peripheral blood source to bone marrow. These survey items were scored on a 5 -point Likert scale from very important to very unimportant Reliability: Not reported; Validity: Not reported Korall, 2017, 2018 [ 64 , 65 ] One study—two reports Canada 13 long-term care homes Cross-sectional study Paid care providers = 529 Age in years ( n (%)): 20–29 = 42 (7.9%); 30–39 = 87 (16.4%); 40–49 = 149 (28.2%); 50–59 = 187 (35.3%); 60–69 = 46 (8.7%); Missing/unknown = 18 (3.4%) Reported Gender: Female = 474 (89.6%); Male = 40 (7.6%); Missing/unknown = 15 (2.8%) Interpreted as: Sex Professions: Health care assistant/resident care aide = 290 (54.8%); Licensed practical nurse = 84 (15.9%); Registered nurse = 40 (7.6%) Resident care coordinator = 13 (2.4%); Manager = 14 (2.6%); Recreational/occupational/ physiotherapist = 24 (4.5%); Unit/program clerk = 18 (3.4%); Missing/unknown = 49 (9.3%) Innovation: Hip protectors are protective undergarments with either a hard shield or soft pads sewn into its sides to cover the skin over the lateral aspects of the proximal femur. The purpose of hip protectors is to minimize the injury to the hip resulting from a fall Study outcome measurement Measures: A 15-item questionnaire titled as C-Hip Index, developed and tested for psychometric properties by authors [ 64 ] to measure affective and cognitive, behavioural and overall hip protector commitment Reliability: α (range) = 0.87–0.97 Validity: (1) Construct validity: Authors reported a two-factor structure as the result of an exploratory factor analysis: Factor 1 (affective and cognitive commitment) and Factor 2 (behavioural commitment) which loaded to a higher order factor called "commitment to hip protectors" with an eigen value of 1.386.…”
Section: Resultsmentioning
confidence: 99%
“…Measures: A 15-item questionnaire titled as C-Hip Index, developed and tested for psychometric properties by authors [ 64 ] to measure affective and cognitive, behavioural and overall hip protector commitment…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations